Feasibility of (18)F-Fluorodeoxyglucose radiotracer dose reduction in simultaneous carotid PET/MR imaging - Eldib, Mootaz (Am J Nucl Med Mol Imaging, 2015)
The purpose of this study was to develop and validate low dose (18)F-FDG-PET acquisition protocols for detection of inflamed carotid plaques specifically for simultaneous PET/MR imaging. The hypothesis was that increasing the duration of the PET acquisition to match that of the MR acquisition might allow for the use of lower levels of the radiotracer, while preserving quantification and image quality. Seven subjects were scanned twice at least one week apart on a simultaneous PET/MR scanner using either the standard clinical dose of (18)F-FDG (373 ± 63 MBq) for 8 minutes or a low dose (93 ± 17 MBq) for 75 minutes. A maximum absolute percent difference of only 4.17% and 7.49% in the left and right carotid TBR was found between the standard dose and four time points of the low dose acquisitions (8, 24, 45, 75 minutes). Only the 8-minute low dose PET data was significantly different in terms of SNR (P = 0.009; % difference = -51%) and qualitative image quality evaluation (P = 0.0005; % difference = -45%). Our preliminary findings indicate that up to 75% reduction of the clinical standard (18)F-FDG dose could be achieved using the proposed acquisition scheme while maintaining accurate quantification and SNR.